(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Oral health significantly influences the overall wellbeing of preschoolers. Misconceptions among parents about the temporary nature of primary teeth often lead to inadequate care, risking long-term dental issues in their children. Previous studies have highlighted gaps in parental awareness regarding the importance of primary teeth and recommended dental practices in Saudi Arabia. This study aims to assess the knowledge and awareness levels of Saudi parents concerning the significance of primary and permanent teeth during mixed dentition. Methods: A cross-sectional study was conducted from August 2024 to November 2024, utilizing a self-structured questionnaire distributed via social media channels. The sample consisted of 708 Saudi parents aged 20 to 60, encompassing various provinces and socioeconomic backgrounds. Statistical analyses were performed to evaluate participant demographics and awareness levels. Results: Among participants, 83.6% recognized the importance of primary teeth, yet 21.5% were unaware of cavity prevention methods, and 56.5% lacked knowledge of space maintainers. While 69.2% acknowledged the potential impact of early tooth loss on permanent teeth alignment, 59.9% believed that the first dental visit should occur after the child's first birthday. Awareness regarding the detrimental effects of nighttime feeding was high, with 66.9% and 72.6% recognizing risks associated with prolonged feeding practices. Demographically, mothers exhibited higher awareness levels than fathers (P = 0.027). Knowledge scores revealed that 41% had high awareness, 35.3% had low knowledge, and 30.8% displayed moderate awareness about the role of primary teeth. Conclusion: Although a significant portion of Saudi parents are aware of the importance of primary teeth, substantial gaps exist in specific dental health knowledge and practices. Targeted educational interventions are imperative to equip parents with vital information regarding preventive dental care, thereby enhancing their children's oral health outcomes. This study underscores the need for comprehensive awareness campaigns to elevate parental understanding and promote better dental hygiene practices for children in Saudi Arabia.